THE DISCREPANCY OF SOCIAL IDENTITY WITH ARABIC COMPETENCE AND THE STUDENTS’ RELIGIOUS ATTITUDE - Muhajir, Muhajir; Jainudin, Cecep (Arabi : Journal of Arabic Studies, 2020)
The organization of Indonesian Muslim Student Action Union (KAMMI) of UIN Mataram is one of the student organizations that often use some Arabic vocabularies in its communication. The research would see the existence of Arabic language in this organization including competence, transformation of social identity and the relationship of the religious attitude of its members. The study used the social identity theory and the models of religious attitudes. The result showed that the Arabic competence of KAMMI members was not very high. The Arabic language frequently used by KAMMI members becomes their social identity even though it is only at a limited level of communication. Their religious attitude was categorized as an exclusive category with accompanying attributes such as code switching of Arabic language in daily dialogue, wearing labelled syar‘i clothes and make themselves feel to be more Islamic with these attributes.